Peningkatan Partispasi Aktif dan Hasil Belajar Matematika melalui Model Pembelajaran Problem-Based Learning pada Siswa SMP - Yuyun Nur Ihwani; Nurul Azisah (Advances In Education Journal, 2026)
This study aims to improve students’ active participation and mathematics learning outcomes through the implementation of the Problem-Based Learning (PBL) model in Grade VIII students of UPT SMP Negeri 3 Galesong Selatan. The background of this study is the low level of student engagement in the learning process and mathematics achievement that has not yet reached the minimum mastery criteria. This research employed a Classroom Action Research design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 31 students of class VIII A. Data were collected through observation sheets of student activities and learning achievement tests at the end of each cycle. The results showed that in Cycle I, student learning mastery reached 25%, while in Cycle II it increased to 84%. In addition, students’ active participation in discussions, group work, and problem-solving activities also improved. These findings indicate that the implementation of the PBL model is effective in improving students’ active participation and mathematics learning outcomes. Therefore, PBL can be used as an alternative learning model to create a more active, meaningful, and problem-oriented mathematics learning environment.